Variation in Internal Space Surface Colors and its Possible Effect on Human Biological Responses in Daylight Conditions. (November 2015) - Hartman, P.; Maňková, L.; Hanuliak, P.; Hraška, J.
Abstract: The significance of the non-visual human response on light, also known as circadian efficiency of light has been rising as the new medical facts were emerging during last decade. The major difference between visual and non-visual (circadian) responses on light is in the way of its perceiving. Biological stimulation depends on quantitative and qualitative properties of light, which penetrates directly into the human eye in contrast to visual stimulation depending more on the amount of the light reflected from the observed surfaces. Natural daylight which dominates in blue region is the most effective in control of our biological response [1]. The paper deals with experimental measuring on three models of deep office room intended for permanent workplace and exposed only to natural daylight. During the experiment, there were monitored modifications in internal daylight spectral properties influenced by internal coloured surfaces and subsequently evaluated for its biological response. This was made in six different positions varying in the distance from the window opening. The measurement proved noticeable rising of negative effect on biological response increasing with distance from window. On the basis of calculation method defined by Rea et al.[2] white colored surfaces provided in the depth of the modeled room of 6 m more than 20% more effective biological stimulation in the direction of view toward window and more than 50% in direction of view toward wall in comparison to yellow and orange surface colors. Through this experiment, there is an effort to draw attention to possible negative effect of inappropriate selection of the color of internal surfaces in regularly occupied spaces. The indoor environment surrounded by surfaces with inappropriate color selection may provide efficient visual comfort, but at the same time, it may negatively modify the spectrum of daylight, what can results in delayed insufficient biological stimulation.